Mentoring and Microteaching training in Al Qur'an Learning for Adults for Al Qur'an Teachers at MQ Al Muhajirin Sidoarjo - Nisak, Nur Maslikhatun; Astuti, Ruli; Nastiti, Dwi; Supriyanto, Eko Budi (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2025)
This community service program aims to improve the teaching competence of Al-Qur’an teachers in delivering learning specifically designed for elderly learners. The program involved several stages, including needs identification, collaborative planning, implementation of mentoring and training, joint reflection and evaluation, as well as program improvement and adjustment. The community service method employed a Participatory Action Research (PAR) approach and was conducted at MQ Al Muhajirin Boro, Tanggulangin. During the needs identification stage, the service team carried out observations, interviews, and discussions to understand the challenges faced by Al-Qur’an teachers in teaching elderly learners, such as difficulties in delivering material, a lack of appropriate teaching techniques, and limited learning support tools. Based on these findings, a microteaching module tailored to the needs of elderly learners was developed, along with a schedule of regular training sessions and the provision of relevant instructional aids and learning media. The mentoring and training activities were conducted periodically, emphasizing the use of visual and audio methods, adequate time intervals, and simple language. Periodic evaluations indicated improvements in teachers’ instructional skills, elderly learners’ understanding of Al-Qur’an materials, and the effectiveness of instructional aids and learning media. Overall, the program produced a significant positive impact and is expected to serve as a model for similar programs in other settings. Recommendations for program sustainability include continuous development, advanced training, community involvement, facility enhancement, and further research.